Acts of Becoming: An Examination of the Historical Symbolism and Embodied Empathy in Detroit: Become Human - Tompkins, Adam (Loading, 2021)
This article examines the rich historical subtext in the future-focused storylines of Quantic Dream’s 2018 release Detroit: Become Human (PS4) and illuminates many of the thematic continuities in racial issues between the past and the future. Much of the subtle historical symbolism appears to have went unnoticed by many reviewers who maligned the videogame and its creator David Cage for relying on lazy tropes that clunkily connect the African American civil rights movement to the narrative of woke androids engaging in a struggle for greater equality in society. Following scholarship that has examined the development of racialized thought in the past, this essay recognizes “race” as a powerful, yet malleable social construct, that sometimes changes over time. Racial concepts in the game do not perfectly align with historical or contemporary understandings of “race” in the United States. Androids, in short, all belong to the same “race.” This article then contends that the storylines of all three playable characters in the game resonate with well-crafted historical parallels and that the narrative geography in the gameworld often closely tethers to the historical geography of Detroit. The characters Markus, Connor, and Kara have intertwining stories that represent different elements of minority life in the United States with the clearest parallels to the historical experience of African Americans. Detroit: Become Human, nonetheless, is a science fiction game about androids. Framing the struggle for equal rights in the future with a group of beings that do not yet exist has the potential to disarm gameplayers of latent biases that may otherwise color their view of contemporary racial issues. The article asserts that the wedding together of past and future through experiential gameplay nurtures an empathic understanding of minority concerns that may carry over to the present to impact understandings of contemporary racial issues.